THE ROLE OF ICT DEVELOPMENT IN PROMOTING CONTROL OF CORRUPTION: EVIDENCE FROM ASEAN COUNTRIES - Naila Erum; Vu Thi Thanh Binh; Sri Delasmi Jayanti (Journal of Applied Finance and Accounting, 2025)
Corruption remains a pervasive global challenge that undermines government quality, hampers economic development, and erodes public trust, particularly in developing and emerging economies. Rapid advancements in information and communication technology (ICT) have been extensively advocated as a strategic tool for enhancing transparency and combating corruption. Nonetheless, current empirical evidence regarding the ICT-corruption relationship is weak and frequently restricted to single-country studies, linear assumptions, or brief observation durations. This study examines the long-term and short-term impacts of ICT growth on corruption control (CoC) in ASEAN nations, utilizing a balanced panel dataset from 1984 to 2023. This study utilizes the panel Autoregressive Distributed Lag (ARDL) methodology to account for dynamic adjustments and cross-country variability, accommodating various orders of integration. The findings indicate a non-linear, inverted U-shaped relationship between ICT development and corruption control, suggesting that initial ICT expansion enhances corruption control but may lead to declining and potentially negative impacts beyond a specific threshold.  This study contributes to the literature and provides policy-relevant insights by emphasizing the importance of balanced and context-sensitive digital governance strategies that enhance transparency and accountability while mitigating unintended governance risks.